FOSTERING LEARNER AUTONOMY THROUGH DIGITAL TOOLS IN EFL CLASSROOMS (International Conference on Medical Science, Medicine and Public Health, 2025)
In the rapidly evolving landscape of language education, fostering learner autonomy has become a central goal in English as a Foreign Language (EFL) classrooms. This study explores how digital tools can effectively promote autonomous learning among EFL students by offering personalized, interactive, and self-directed learning experiences. Through a review of current pedagogical practices and the integration of various digital platforms—including language learning apps, online collaboration tools, and learning management systems—the research highlights the transformative potential of technology in supporting learners to take control of their language development. Findings suggest that when digital tools are thoughtfully implemented, they not only enhance motivation and engagement but also improve learners' ability to set goals, monitor progress, and reflect on their learning. The paper concludes with practical recommendations for educators aiming to cultivate autonomous learning environments through digital integration.